Food Habits in adolescents of the district “Mi Peru”, Callao Region: Hábitos alimenticios en adolescentes del distrito Mi Perú, Región Callao - Morales, Juan (2017)
OBJECTIVES: To assess of alimentary habits in adolescents of “Mi Perú” district. MATERIALS AND METHODS: Descriptive cross-sectional study developed in 2013. Participated 459 students of 4th and 5th grade coming from the state high school of Mi Peru distric, in the Callao Region. We used a questionnaire composed of 26 questions about omission and repetition of meals, add salt to food; fast food, junk food and fruits and vegetables consumption, company during meals, food consumption place, rate of food intake , nap after lunch, interval between dinner and bedtime and watch TV during meals. RESULTS: Of total 459 adolescents, 50,1% (n=230) were men and 49,9 % (n=229) were women between 14 and 19 years old (average age 16,1 years; SD: 0,92). 44,3 % (n = 203) of adolescents were found within the category of “change habits”, while 55,7 % (n = 256) were within the category of “conserving habits”. By gender, higher proportion of men belonging to the category of “change habits” with 47,8% compared to 40,6% of women, no statistically significant difference (p = 0,120) were found. CONCLUSIONS: 44,2 % of adolescents require changing your eating habits, being in greater proportion in males.